2021
DOI: 10.1111/socf.12748
|View full text |Cite
|
Sign up to set email alerts
|

“The Books Make You Feel Bad”: Expert Advice and Maternal Anxiety in the Early 21st Century*

Abstract: With ethnographic observations and in-depth interviews of parenting classes serving middle-and uppermiddle-class mothers, this paper explores how mothers engage and experience expert advice. Contemporary models of motherhood expect more than nurture and sacrifice; modern mothers must also be highly skilled and well informed. A wealth of information is available to help mothers navigate a high-pressure environment in which their actions are believed to have deep, long-lasting impact on children's future health,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This socially constructed and historically specific set of norms calls upon mothers to engage in an expert‐informed style of mothering that is time‐intensive and expensive. As a culturally dominant set of norms it has fueled divisiveness and anxiety about mothering in which mothers encounter social judgment for their mothering techniques and second guess their mothering strategies (Cucchiara & Steinbugler, 2021; Henderson et al., 2016). In its intensification of mothering standards, this ideology has also contributed to the “mommy wars” in which working moms are pitted against stay‐at‐home mothers in a contest to see which group can achieve the highest mothering standards (Abetz & Moore, 2018; Crowley, 2015; Pedersen, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This socially constructed and historically specific set of norms calls upon mothers to engage in an expert‐informed style of mothering that is time‐intensive and expensive. As a culturally dominant set of norms it has fueled divisiveness and anxiety about mothering in which mothers encounter social judgment for their mothering techniques and second guess their mothering strategies (Cucchiara & Steinbugler, 2021; Henderson et al., 2016). In its intensification of mothering standards, this ideology has also contributed to the “mommy wars” in which working moms are pitted against stay‐at‐home mothers in a contest to see which group can achieve the highest mothering standards (Abetz & Moore, 2018; Crowley, 2015; Pedersen, 2016).…”
mentioning
confidence: 99%
“…Many mothers wish to enact motherhood in a perfect manner, with social media raising the stakes of this pursuit in ways that have important implications for mental health (Henderson et al., 2016; Schoppe‐Sullivan et al., 2017). Attempting to always make the right decisions, mothers consult expert advice, but find it often fuels rather than quiets the anxiety surrounding motherhood (Cucchiara & Steinbugler, 2021). In light of these pressures, this line of research has shown how intensive mothering norms contribute to guilt, anxiety, post‐natal depression, poor mental health, and exhaustion among mothers and conflict among couples (e.g., Chesley, 2011; Gunderson & Barrett, 2017; Henderson et al., 2016; Loyal at el., 2021; Sonnenberg & Miller, 2021).…”
mentioning
confidence: 99%